Gardening as the dominant leisure time physical activity (LTPA) of older adults from a post-communist country. The results of the population-based PolSenior Project from Poland. Issue 3 (May 2015) - Rowinski, Rafal; Dabrowski, Andrzej; Kostka, Tomasz
Highlights We describe the LTPA of older Polish citizens. Only 33.6% fulfilled the recommended LTPA criteria. Polish elders rarely participate in organized, intentional forms of LTPA. Gardening (64.6%), walking (39.0%) and cycling (37.3%) are the most popular activities. Sustaining existing favorable LTPA habits seems essential for health policy.